{μ-2,2′-(Ethane-1,2-diyl)bis[4,6-bis(trimethylsilyl)-1,3-dihydrocyclopenta[c]pyrrol-5-one]}bis[tricarbonyliron(0)] - Hilario D. Huerta-Zerón; Anke Spannenberg; Matthias Beller; Henrik Junge (IUCrData, 2023)
The binuclear title compound, [Fe2(C28H48N2O2Si4)(CO)6], consists of two central iron(0) atoms, each of them surrounded by a cyclopentadienone moiety and three carbonyl ligands in a three-legged piano-stool shape. Furthermore, the bis(cyclopentadienone) ligand acts as a bridge between the two metal atoms.